Pengembangan LKPD Matematika HOTS (Higher of Order Thinking Skills) Berorientasi Kearifan Lokal Daerah untuk Sekolah Dasar - Sulistyani, Nawang; Deviana, Tyas (Jurnal Ilmiah Mandala Education (JIME), 2021)
The improvement 2013 curriculum has implications for the exit of mathematics from thematic learning. However, this separation don’t ignore 4C skills which include critical, creative, collaborative, and communication. One of these skills can be achieved through HOTS (Higher of Order Thingking Skills) learning. One of the HOTS learning achievements, which is proven through student learning activities that reflect learning with high level thinking skills. One of the teaching materials which contains various learning activities is the Student Activity Sheet (LKPD). The purpose of this research is to produce a HOTS Mathematics Student Worksheet which is oriented towards local of Malang city for elementary schools which is valid, interesting, practical and effective. The research method used was the Dick & Carey research and development model. The subjects of this study were all 5th students of SD Muhammadiyah 5 Malang. The type of data used is qualitative data obtained from the validation responses of experts, teachers and students in the form of suggestions for improvement, while quantitative data is obtained from the results of learning activities of students and the calculation of the response questionnaire validation from experts, teachers and students. Based on the results of field trials, it was found that the HOTS Mathematics Worksheet was oriented towards local wisdom of Malang City which was developed to be very valid, interesting, practical and effective in facilitating students in a more meaningful mathematics learning which is integrated with the environment around the students.